PENGARUH EMOSIONAL, TEKNOLOGI DAN SUKU BUNGA TERHADAP KEPUASAN NASABAH REGULER YANG BERDAMPAK TERHADAP LOYALITAS NASABAH PT. BANK SUMSELBABEL PANGKALPINANG - Nadia Sri Rezeki (JEM Jurnal Ekonomi dan Manajemen, 2023)
This study uses a quantitative approach. The research sample used was 100 respondents (regular customers) who were then asked to answer the research questionnaire and used as primary data for analysis materials. Methods of data analysis using multiple linear regression analysis and simple regression, with a validity test, reliability test, classical assumption test and test the coefficient of determination. While testing the hypothesis using the F test (simultaneous) and t test (partial). As a tool in data analysis using the SPSS version 25 program. The results of the study concluded that the positive and significant influence of emotional variables, technology and interest rates on customer satisfaction of 0.8410 means 84.10% while the other 15.90% is explained by other variables not included in this study. There is a positive and significant influence of emotional variables on customer satisfaction, there is a positive and significant influence of technology variables on customer satisfaction, there is a positive and significant influence of the interest rate variable on customer satisfaction and there is a positive and significant effect of customer satisfaction on customer loyalty by 70 % while the other 30% is explained by other variables not included in this study. For example, the influence of service quality, product quality, customer trust, and others.